2017
DOI: 10.3389/fmars.2017.00327
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Animal Circadian Clock: Diurnal and Light-Entrained Gene Expression in the Sponge Amphimedon queenslandica

Abstract: The circadian clock is a molecular network that coordinates organismal behavior and physiology with daily environmental changes in the day-night cycle. In eumetazoans (bilaterians + cnidarians), this network appears to be largely conserved, yet different from other known eukaryotic circadian networks. To determine if the eumetazoan circadian network has an older origin, we ask here whether orthologs comprising this network are expressed in a manner consistent with a role in regulating circadian patterns in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 33 publications
8
45
0
1
Order By: Relevance
“…Cryptochromes are blue-light sensing flavoproteins (53) that have a well-characterised role in regulating circadian rhythms in plants (54), insects (55) and mammals (56). The apparent important role for a cryptochrome in light detection and response presented here is consistent with previous findings in this sponge (12) and in other marine invertebrates (45,(47)(48)(49)57). In A. queenslandica, AqCry2 is spatially expressed in the photo-responsive posterior pigment ring (15) that possesses long cilia that act as phototactic rudders, steering larvae away from light (14).…”
Section: A Queenslandica Larvae Are Maintained In the Lightsupporting
confidence: 89%
See 3 more Smart Citations
“…Cryptochromes are blue-light sensing flavoproteins (53) that have a well-characterised role in regulating circadian rhythms in plants (54), insects (55) and mammals (56). The apparent important role for a cryptochrome in light detection and response presented here is consistent with previous findings in this sponge (12) and in other marine invertebrates (45,(47)(48)(49)57). In A. queenslandica, AqCry2 is spatially expressed in the photo-responsive posterior pigment ring (15) that possesses long cilia that act as phototactic rudders, steering larvae away from light (14).…”
Section: A Queenslandica Larvae Are Maintained In the Lightsupporting
confidence: 89%
“…Indeed, sponge larvae are known to prefer shaded surfaces for settlement (13) and this is consistent with A. queenslandica larvae being negatively phototactic immediately post-emergence (14, but see 3). The phototaxis is regulated by a blue-light flavoprotein, a cryptochrome, which is localised to cells of the posterior photosensory organ in precompetent larvae, prior to their emergence from the adult (12,15). These observations raise the hypothesise that two interdependent sensory systemsa photosensory cryptochrome and a chemosensory systemorchestrate the pelago-benthic transition in this species.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Species from early diverging animal phyla have been studied to characterize the mechanisms of photoreception and signal transduction as well as the potential for a circadian clock (Plachetzki, Fong, & Oakley, ). Research with sponges has shown that various species have light‐dependent behaviour (Leys, Cronin, Degnan, & Marshall, ) as well as the molecular components for photoreception (cryptochromes; Rivera et al, ), components of the classic bilaterian circadian clock (Jindrich et al, ; Simionato et al, ) and cyclical oscillations in gene expression of these clock genes under diel lighting conditions (Jindrich et al, ). Similarly, light has a significant impact on the behaviour of ctenophores and previous studies have shown they have various light sensing proteins encoded in their genome (Schnitzler et al, ), but the potential for a circadian clock has not yet been studied (Reitzel et al, ).…”
Section: Introductionmentioning
confidence: 99%